2016
DOI: 10.1016/j.kontakt.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Academic and clinical stress, stress resources and ways of coping among Turkish first-year nursing students in their first clinical practice

Abstract: Nursing students face both physical and psychosocial risks such as job stress at work during the training period. The aim of the study was to determine the academic and clinical stress, and the ways first-year nursing students cope in their first clinical practice. Methods: A descriptive, cross-sectional design was used. This study was carried out in the nursing department of Giresun University in Giresun, Turkey. The sampling consisted of 109 nursing students who agreed to participate in this study in the 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
9

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 33 publications
0
16
0
9
Order By: Relevance
“…Menurut Yang and Smith (2016) salah satu yang menjadi masalah akademik adalah ketakutan kegagalan, lingkungan yang kompetitif dan beban yang berat. Sumber stres pada bidang akademik adalah banyaknya tugas yang harus dikerjakan, kurikulum dengan beban yang tinggi, persaingan antar teman untuk mendapatkan nilai yang tinggi dan banyaknya bahan materi yang harus dipelajari dan dikuasai oleh mahasiswa perawat (Bahadir, 2016;Zhang et al, 2017).…”
Section: Faktor Yang Menyebabkan Stres Akademikunclassified
See 2 more Smart Citations
“…Menurut Yang and Smith (2016) salah satu yang menjadi masalah akademik adalah ketakutan kegagalan, lingkungan yang kompetitif dan beban yang berat. Sumber stres pada bidang akademik adalah banyaknya tugas yang harus dikerjakan, kurikulum dengan beban yang tinggi, persaingan antar teman untuk mendapatkan nilai yang tinggi dan banyaknya bahan materi yang harus dipelajari dan dikuasai oleh mahasiswa perawat (Bahadir, 2016;Zhang et al, 2017).…”
Section: Faktor Yang Menyebabkan Stres Akademikunclassified
“…Karakteristik individu merupakan masalah personal yang berkontribusi terhadap stres akademik. Karakteristik individu terdiri dari jenis kelamin, kondisi psikologis, ketahanan atau kekuatan diri, tingkat spiritual serta kecerdasan emosional dan ketahanan (Bahadir, 2016). Mahasiswa yang mampu beradaptasi terhadap lingkungan yang baru yaitu klinik akan bisa menyesuaikan diri dan bertahan terhadap lingkungan klinik.…”
Section: Faktor Yang Menyebabkan Stres Akademikunclassified
See 1 more Smart Citation
“…1 These academic and clinical stressors can be triggered by examination preparation, course workload, paying course fees, not meeting personal needs, heavy workload, taking care of patients, being criticized by teachers, encountering a dying patient, the fear of making practice errors and experiencing bullying and discrimination in clinical settings. [1][2][3][4] It has been demonstrated that nursing students use a variety of both adaptive and maladaptive coping strategies to manage these academic and clinical problems. 5 Particularly in relation to stress and coping, the psychological well-being of nursing students is an important focus of nurse education research.…”
mentioning
confidence: 99%
“…better time management, communication skills, better self-training, high activeness, and comprehensive selfconcept, and better promote the employability after the graduation. Yilmaz (2016) indicated that a student with internship could faster fi nd a job, after the graduation, than those without internship; students could acquire working experience in real world to further enhance the employability. In this case, the following hypothesis is proposed in this study.…”
Section: Research Hypothesismentioning
confidence: 99%